Happiness and loss aversion: when social participation dominates comparison - Maarten C. M. Vendrik; Geert Woltjer (Institute for the Study of Labor (IZA), 2006)
A central finding in happiness research is that a person's income relative to the average income in her social reference group is more important for her life satisfaction than the absolute level of her income. This dependence of life satisfaction on relative income can be related to the reference dependence of the value function in Kahneman and Tversky's (1979) prospect theory. In this paper we investigate whether the characteristics of the value function like concavity for gains, convexity for losses, and loss aversion apply to the dependence of life satisfaction on relative income. This is tested with a new measure for the reference income for a large German panel for the years 1984-2001. We find concavity of life satisfaction in positive relative income, but unexpectedly strongly significant concavity of life satisfaction in negative relative income as well. The latter result is shown to be robust to extreme distortions of the reported-life-satisfaction scale. It implies a rising marginal sensitivity of life satisfaction to more negative values of relative income, and hence loss aversion (in a wide sense). This may be explained in terms of increasing financial obstacles to social participation.
Keywords: I31; D6; 330; life satisfaction; relative income; value function; loss aversion; social participation